THE INFLUENCE OF MODERN DANCE ON THE PHYSICAL HEALTH INDICATORS OF YOUNG ADOLESCENTS - Кholchenkova N. M. (International Journal of Innovative Technologies in Social Science, 2020)
The article describes modern dance as an effective means of healthcare of children and youth in the educational process, which contributes a lot to the formation of physical health. The influence of modern dance on the formation of such physical qualities as flexibility, strength, endurance, speed, agility and motor coordination is determined. To diagnose the level of physical health formation for younger teens, school anxiety assessment of the somatic health level of schoolchildren aged 7-16 years (by Krutsevich , Apanasenko, 1999) was used. The results of processing the data obtained during the formative stage of experiment are presented in the paper. It was found that author’s method of teaching modern dance was effective.